ผลของกลุ่มบำบัดประคับประคองต่อภาระการดูแลและภาวะซึมเศร้าในผู้ดูแลผู้ป่วยจิตเภท - เกษมสุข, ปาณิสรา; อุทิศ, เพ็ญพักตร์; แดงด้อมยุทธ์, เพ็ญนภา (Thai Red Cross Nursing Journal, 2008)
การวิจัยนี้เป็นการวิจัยกึ่งทดลองแบบสองกลุ่มวัดก่อนและหลังการทดลอง มีวัตถุประสงค์เพื่อศึกษาผลของโปรแกรมกลุ่มบำบัดประคับประคองต่อภาระการดูแล และภาวะซึมเศร้าของผู้ดูแลผู้ป่วยจิตเภท กลุ่มตัวอย่าง คือ ผู้ดูแลที่นำผู้ป่วยจิตเภทมารับการรักษาที่แผนกผู้ป่วยนอก โรงพยาบาลจิตเวชขอนแก่นราชนครินทร์ ซึ่งได้รับคัดเลือกแบบเจาะจงตามเกณฑ์คุณสมบัติจำนวน 40 คน และจับคู่ตามช่วงอายุและประเภทของความสัมพันธ์กับผู้ป่วย แบ่งเป็นกลุ่มทดลองและกลุ่มควบคุม กลุ่มละ 20 คน กลุ่มทดลองได้รับการดูแลด้วยโปรแกรมกลุ่มบำบัดประคับประคองที่ผู้วิจัยสร้างขึ้น ส่วนกลุ่มควบคุมได้รับการดูแลตามปกติ เครื่องมือที่ใช้ในการวิจัย คือ โปรแกรมกลุ่มบำบัดประคับประคอง แบบวัดภาระการดูแล และแบบวัดภาวะซึมเศร้า เครื่องมือ 2 ชุดหลังมีค่าความเที่ยงสัมประสิทธิ์อัลฟ่าของครอนบาค เท่ากับ .88 และ .82 ตามลำดับ วิเคราะห์ข้อมูลโดยใช้สถิติทดสอบที ผลการวิจัยที่สำคัญ สรุปได้ดังนี้ 1. ภาระการดูแลและภาวะซึมเศร้าของผู้ดูแล หลังได้รับโปรแกรมกลุ่มบำบัดประคับประคอง ต่ำกว่าก่อนได้รับโปรแกรมฯ อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 2. ภายหลังการทดลอง พบว่าภาระการดูแลและภาวะซึมเศร้าของผู้ดูแลกลุ่มที่ได้รับโปรแกรมกลุ่มบำบัดประคับประคอง ต่ำกว่ากลุ่มที่ได้รับการพยาบาลตามปกติ อย่างมีนัยสำคัญทางสถิติที่ระดับ .05 Effects of Support Group Therapy on the Burden and Depression of Caregivers of Patients with Schizophrenia This pre-post control group quasi-experimental research aimed at determining the effects of using the support group therapy program on the burden and depression of caregivers of patients with schizophrenia. A research sample comprised 40 caregivers who accompanied schizophrenia patients to the out-patient unit at Khon Kaen Rajanagarindra Psychiatric Hospitaland who met the inclusion criteria. They were matched according to gender and their relationships with patients and then equally assigned into the experimental group and the control group, with 20 subjects in each group. The research instruments were the support group therapy program, developed by the researcher, the Caregiver Burden Scale, and Beck Depression Inventory. The Cronbach’s Alpha Coefficient reliability of the two latter instruments were .88, and .82, respectively. The t-test was used in data analysis. The major findings were as follows: 1. The burden of caring and the depression of the caregivers of schizophrenia patients who participated in the support group therapy program were significantly lower than that before at the .05 level. 2. After the experiment, the burden of caring and the depression of caregivers of schizophrenia patients who participated in the support group therapy program were significantly lower than those caregivers who participated in the regular caring activities at the .05 level.